Cognitive Style and Frame Susceptibility in Decision-Making - Mandel, David R.; Kapler, Irina V. (Frontiers in Psychology, 2018)
The susceptibility of decision-makers’ choices to variations in option framing has been attributed to individual differences in cognitive style. According to this view, individuals who are prone to a more deliberate, or less intuitive, thinking style are less susceptible to framing manipulations. Research findings on the topic, however, have tended to yield small effects, with several studies also being limited in inferential value by methodological drawbacks. We report two experiments that examined the value of several cognitive-style variables, including measures of cognitive reflection, subjective numeracy, actively open-minded thinking, need for cognition, and hemispheric dominance, in predicting participants’ frame-consistent choices. Our experiments used an isomorph of the Asian Disease Problem and we manipulated frames between participants. We controlled for participants’ sex and age, and we manipulated the order in which choice options were presented to participants. In Experiment 1 (N = 190) using an undergraduate sample and in Experiment 2 (N = 316) using a sample of Amazon Mechanical Turk workers, we found no significant effect of any of the cognitive style measures taken on predicting frame-consistent choice, regardless of whether we analyzed participants’ binary choices or their choices weighted by the extent to which participants preferred their chosen option over the non-chosen option. The sole factor that significantly predicted frame consistent choice was framing: in both experiments, participants were more likely to make frame consistent choices when the frame was positive than when it was negative, consistent with the tendency towards risk aversion in the task. The present findings do not support the view that individual differences in people’s susceptibility to framing manipulations can be substantially accounted for by individual differences in cognitive style.